Investasi Dan Hak Masyarakat Lokal Dalam Perspektif Bisnis Dan Hak Asasi Manusia - Bangun, Budi Hermawan; Kurniawan, Heru Yudi (Res Judicata, 2023)
This research aims to provide an overview of the relationship between business and human rights and discuss how investment activities carried out by corporations must respect and fulfill the rights of local communities in their business areas and how the government should balance investment interests and the rights of local communities. By prioritizing secondary data, which was then analyzed qualitatively to draw conclusions and provide prescriptions, it was found that businesses have a responsibility to respect, protect, and fulfill human rights in all their activities. The government has a key role in maintaining a balance between investment interests and the rights of local communities. They must regulate and supervise investments to ensure that they contribute to sustainable development and protect the rights of local communities.Keywords: Investment, Local Communities, Human Rights.